Strategi Kreativitas dan Profesionalitas Makeup Artist dalam Meningkatkan Kualitas Layanan Kecantikan - Maria Krisnawati; Taofan Ali Achmadi; Zahra Hafizshah; Maulida Firda Ayuningsih; Kusuma Wardhani; Afifah fahri Rofina; Eva Liantira Dinasa; Amila Putri Hunafa; Fitriya Nur Rahma (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The beauty industry is growing rapidly as public interest in appearance and self-confidence increases, leading to a rising demand for makeup artist (MUA) services. In this context, creativity and professionalism are crucial factors for MUAs to produce high-quality makeup and provide satisfactory service to clients. This study aims to understand the strategies of creativity and professionalism employed by makeup artists to enhance the quality of beauty services. The method used is descriptive qualitative research, with data collection techniques including observation, interviews, and documentation. The results indicate that service strategies such as understanding client needs, effective communication, personal branding, and the use of social media can enhance customer trust and loyalty. Additionally, mastery of makeup techniques such as complexion, contouring, highlighting, color palette selection, and adapting makeup looks to face shapes and occasions significantly influences the quality of the final makeup result. By combining creativity, technical skills, and a professional attitude, makeup artists can improve the quality of beauty services and strengthen their competitiveness in an increasingly competitive beauty industry.